1999
DOI: 10.1067/msy.2099.100381
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the metastasis suppressor gene KAI1 in advanced colon cancer and its metastases

Abstract: These data demonstrate that the KAI1 mRNA expression and the KAI1 protein level increase in an earlier tumor stage of colorectal cancer, decrease in advanced stages, and are lost in metastases. The loss of KAI1 might favor the ability of colorectal cancer cells to metastasize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…Although anti-CD82 antibodies come from 10 companies, the subjects of 5 countries are involved in our study, and different statistical methods are employed, CD82 expression and its correlation with clinicopathological parameters are comparatively consistent, indicating that these antibodies mainly recognize CD82 protein and its expression is independent of population or not determined by statistics. It was noted that CD82 mRNA overexpression was observed in gastric cancer according to bioinformatics analysis, in agreement with the finding about thyroid papillary carcinoma [56] and colorectal cancer [57]. The discrepancy might be due The bias was analyzed about risk degrees of CD82 expression in gastric mucosa (A) for gastric carcinogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…Although anti-CD82 antibodies come from 10 companies, the subjects of 5 countries are involved in our study, and different statistical methods are employed, CD82 expression and its correlation with clinicopathological parameters are comparatively consistent, indicating that these antibodies mainly recognize CD82 protein and its expression is independent of population or not determined by statistics. It was noted that CD82 mRNA overexpression was observed in gastric cancer according to bioinformatics analysis, in agreement with the finding about thyroid papillary carcinoma [56] and colorectal cancer [57]. The discrepancy might be due The bias was analyzed about risk degrees of CD82 expression in gastric mucosa (A) for gastric carcinogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…However, in prostate cell lines, induction of p53 with DNA damaging agents did not increase KAI1 expression. So, it remains questionable whether KAI1 is the primary target of the tumour suppressor protein p53 (Adachi et al 1996;Mashimoto et al 1998;Maurer et al 1999;Jackson & Puisieux 2000;Shinohara et al 2001).…”
Section: Kiss1mentioning
confidence: 99%
“…Our results showing the elevated expression of claudin-1, −3 and −4, EpCAM, E-cadherin in colon cancer were consistent with earlier studies [11,22,23] . Previously it was shown that decreased expressions of CD9 [24] and CD82 were vital for colon cancer metastasis, and particularly reduced expression of CD82 was related with metastatic colon [25] and gastric cancer [26]. Here, we have also identified expression changes in seven PKC isoforms in both normal colon cells and colon cancer cells.…”
Section: Discussionmentioning
confidence: 56%